Decentralised School System through Community Participation From Expectation to Implementation - Bhue, Prakash; Singh, Tattwamasi Palta (JOURNAL OF INDIAN EDUCATION, 2020)
Decentralisation plays a vital role in school management. It makes local community involved in planning and decision making in school affairs at grassroot level. After the commencement of Right of Children to Free and Compulsory Education Act (RTE), 2009 the importance of School Management Committee (SMC) was seriously taken into consideration, though the community participation had earlier existed with different nomenclature. The emphasis on SMC at the school level has been laid to actualise the goal of Universalisation of Elementary Education (UEE). Despite growing emphasis on SMC, there is a gap between the planning and implementation process of community participation in real sense. The paper makes an attempt to examine the nature of challenges confronted by the SMC members from two broad perspectives; (i) set of external issues which are beyond the margin of members and (ii) set of internal issues which exist among them. In the last section, based on some empirical evidences the paper suggests some measures with policy implications for effective functioning of SMCs.